Relasi media sosial dan minat menikah Generasi Z dalam perspektif pertukaran sosial - Risma Nur Fitria; Siti Komariah; Puspita Wulandari (Dimensia: Jurnal Kajian Sosiologi, 2024)
The rapid growth of technology has given rise to new phenomena, one of which is news related to infidelity which is widely circulating on social media. The rise in these cases often makes the younger generation afraid to get married. This research aims to determine the younger generation's interest in getting married after being exposed to the issue of infidelity on social media. The method used in this research is a quantitative method with a phenomenological approach. This research uses data collection techniques with a random sampling approach. From the research results, it can be concluded that the issue of infidelity on social media has a significant influence on the decline in the younger generation's interest in getting married with a percentage of (35.3%) agreeing and (5.9%) strongly agreeing. Apart from that, the issue of infidelity on social media also influences the younger generation's views on marriage with a percentage of (50%) agreeing and (11.8%) strongly agreeing.